Examining The Effects of Economic Growth on Unemployment in Indonesia - Teddy Ch Leasiwal; Hermi Oppier; Ali Tutupoho; Adellci Palloma (Syntax Corporation Indonesia, 2022)
This study aims to determine the effect of the variables of Economic Growth, Minimum Wage, and Human Development Index on the Unemployment Rate in Indonesia in the short and long term. This research uses quantitative research. The data used is secondary data from 2001 to 2020. The dependent variable in this study is Unemployment while the independent variables are Economic Growth, Minimum Wage, and Human Development Index. The analytical method used in this research is the Vector Error Correction Model (VECM). The results showed that the variable economic growth had a positive and significant impact on the unemployment rate in the short and long term. The minimum wage variable and the human development index variable in the short and long term respectively have a negative and insignificant impact. Moreover, This research provides good and appropriate information for academics and the government to be able to reduce the problem of unemployment in Indonesia by using an economic and social approach.